Barreira funcional intestinal, absorção e biodisponibilidade de rifampicina, isoniazida e pirazinamida em pacientes com tuberculose pulmonar ativa - Façanha, Mônica Cardoso (2007)
Reduced antituberculosis drugs concentrations are associated with Mycobacterium tuberculosis resistance, mostly in patients in irregular but also in directly observed treatment. This study aims to evaluate intestinal permeability and bioavailability of rifampin (R), isoniazid (I) and pyrazinamide (P) in patients with active pulmonary tuberculosis. A controlled cross sectional study evaluated intestinal permeability from 56 consecutive active pulmonary tuberculosis (TB) patients who attended Carlos Ribeiro Health Unit in Fortaleza, Ceará, northeast of Brazil, from July 2004 to December 2005. The Thirty who first came were selected to have R, I and P serum concentration dosed. Twenty nine healthy controls were select among health professionals, their relatives and neighboring. To access intestinal permeability lactulose/manitol (L/M) test was performed by HPLC in urine samples collected during five hours. To access bioavailability two blood samples were collect at 2 and 6 hours after drug ingestion. Demographic information was recorded from all volunteers. Mean age was 39.2 ± 15 years in cases and 34 ± 11.0 in controls (p=0.61); 71.4% cases and 65.5% controls were men (p=0.57). Lactulose urinary excretion was significantly lower in TB patients (median 0.1721%; range 0.0-5.0139) than in controls (median 0.4301%; range 0.2125-2.064) (p=0.0194); median manitol excretion in cases was 17.9910% (1.9567-71.5446) and in controls, 24.39894% (range 1.3883-63.0539) (p=0.147) and the lactulose/manitol ratio was of 0.0095 (range 0.0-0.0759) in cases and 0.0153 (0.0-0.0136) in controls (p=0.0698). Maximum means seric rifampin concentration in cases was1.46 ± 0.72 µg/ml and in controls, 3.07 ± 6.69µg/ml (p<0.001); maximum means seric isoniazid concentration was 2.62 ± 1.53 µg/ml in cases and 0.76 ± 1.98 µg/ml in controls (p=0.057); maximum means seric pirazinamide concentratio was 44.10 ± 10.40 µg/ml in cases and 12.02 ± 36.32 µg/ml in controls (p=0.007). Four cases (13.3%) had all tested drugs serum concentrations under expected normal; 21/30 (70.0%) had expected normal concentrations only for one drug (pyrazinamide) and 5/30 (16.7%) for 2 drugs only (pirazinamide and isoniazid). None of the cases had expected concentration levels for all 3 drugs, simultaneously. In conclusion, there was lesion in the functional intestinal barrier and malabsorption for rifampin and isoniazid in active pulmonary TB patients suggesting it is necessary a deeper evaluation of measures to reduce malabsorption, since only these drugs are used during last the four months of treatment.